INVENTORY ASSESSMENT METHODS IN TRADING AND MANUFACTURING COMPANIES: AN EMPIRICAL STUDY - Ardiani Ika Sulistyawati; Aprih Santoso; Sri Yuni Widowati; Siti Farikah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
The purpose of the study was to determine the effect of the variability of inventory, company size, intensity inventory, accounting earnings variability, variability in the cost of goods sold and the ownership structure of the inventory valuation method. The valuation method used is the First In First Out (FIFO) and average method. The object of this study is a trading and manufacturing company listed on the Stock Exchange from 2009-2014. There are 50 companies that meet the criteria, 10 companies using the FIFO method and 40 companies use the average method. Statistical analysis tools used in this study is a logistic regression with a significance level of 5%. These results indicate the variability of inventory and company size significantly influence the selection method of inventory valuation. While the intensity of inventory, accounting earnings variability, variability in the cost of goods sold and the ownership structure does not significantly influence the selection method of inventory valuation.